Effects of different sugammadex doses on the train of four ratio recovery progression during rocuronium induced neuromuscular blockade in the rat phrenic nerve hemidiaphragm - Kim, Yong Beom (Korean J Anesthesiol, 2020)
BACKGROUND: In this study, we used an ex-vivo model to investigate the recovery pattern of both the train-of-four (TOF) ratio and first twitch tension of TOF (T1), and determined their relationship during recovery from rocuronium-induced neuromuscular blockade at various concentrations of sugammadex. METHODS: Tissue specimens of the phrenic nerve-hemidiaphragm were obtained from 60 adult Sprague-Dawley rats. Each specimen was immersed in an organ bath filled with Krebs buffer solution and stimulated with the TOF pattern using indirect supramaximal stimulation at 20-second intervals. After a 30-minute stabilization period, rocuronium loading and booster doses were serially administered at 10-minute intervals in each sample until > 95% depression of T1 was confirmed. Specimens were randomly allocated to either the control group (washout) or to one of five sugammadex concentration groups (0.75, 1, 2, 4, or 8 times equimolar doses of rocuronium to produce > 95% T1 depressions; SGX0.75, SGX1, SGX2, SGX4, and SGX8, respectively). Recovery from neuromuscular blockade was monitored using T1 and the TOF ratio simultaneously until the recovery of T1 to > 95% and the TOF ratio to > 0.9. RESULTS: Statistically significant intergroup differences were observed between the recovery patterns of T1 and the TOF ratio (TOFR, P < 0.050), except between SGX2 and SGX4 groups. TOFR/T1 values were maintained at nearly 1 in the control, SGX0.75, and SGX1 groups; however, they were exponentially decayed in the SGX2, SGX4, and SGX8 groups. CONCLUSIONS: Recovery of the TOF ratio may be influenced by the sugammadex dose, and a TOF ratio of 1.0 may be achieved before full T1 recovery if administration of sugammadex exceeds that of rocuronium.